MEASUREMENT OF EMISSION FACTOR AND BIOEFFICATION OF ONE PUSH AEROSOL INSECTICIDIES AGAINST DECEASE OF FEMALES AEDES AEGYPTI - quraisyiyah, sukainah; yuana S.Si.,M.Si, firdy; widodo M.Si.,Ph.D, chomsin (Physics Student Journal, 2014)
At this time more household insecticide marketed in various trademarks, packaging, and active material content. For every instance should be examined the efficacy to the insect and calculated the particle concentration. The particle concetration measurement and bioeffication to 3 one push aerosol repellent product, the first is poduct A with content transfluthrin 21.3%, product B with content metofluthrin 3.5% and product C with content transfluthrin 25%. The test of bioeffication on female Aedes aegypti use the glass chamber with 3 times repetations. And for to known the relationship between emission factor and bioeffication so do the measurement of the particle concentration. Measurement of the particle insectisides concentration of one push aerosol performed using P-Trak models 8525 with 3 times repetations in the glass chamber. The results of bioeffication using glass chamber showed that the percentage of Aedes aegypti mortality on 3 the mosqito product repellent is 100%. The most rapid in Knock-Down Time 50 (KT 50) and KT 90 is Product A and the longest is product C. The results of Particle measurement use P-Trak models 8525 produces the factor emissions are different for each time of spraying. The highest is Product B, then produt A, and the lowest is the product C. Key word : one push aerosol insecticidies, glass chamber, bioeffication, emission factor